2013
DOI: 10.1148/radiol.13121511
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage: Evaluation with Fluid-suppressed 7.0-T Sodium MR Imaging in Subjects with and Subjects without Osteoarthritis

Abstract: Purpose:To assess the potential use of sodium magnetic resonance (MR) imaging of cartilage, with and without fluid suppression by using an adiabatic pulse, for classifying subjects with versus subjects without osteoarthritis at 7.0 T. Materials and Methods:The study was approved by the institutional review board and was compliant with HIPAA. The knee cartilage of 19 asymptomatic (control subjects) and 28 symptomatic (osteoarthritis patients) subjects underwent 7.0-T sodium MR imaging with use of two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 35 publications
8
74
1
Order By: Relevance
“…Ouwerkerk et al (27) found an increased Na + concentration in malignant breast tissue. Yet other studies have used 23 Na MRI to study myocardial infarction (28) and osteoarthritis (29). 23 Na MRI has even been used to study the effect of muscle contraction caused by different kinds of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Ouwerkerk et al (27) found an increased Na + concentration in malignant breast tissue. Yet other studies have used 23 Na MRI to study myocardial infarction (28) and osteoarthritis (29). 23 Na MRI has even been used to study the effect of muscle contraction caused by different kinds of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…related to the occurrence of joint effusion might be problematic in differentiating fluid from cartilage and likely be a substantial source of error in inflammatory arthritis. Future studies addressing these questions will possibly benefit from technical evolutions allowing the suppression of MRI signal from fluid [36] . These findings encourage further efforts towards quantitative standardized MRI of cartilage at high field.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo application of Na-imaging have intrinsically low signal to noise ratio (SNR~20-40), and limited resolution (~2-10 mm isotropic) (31). Several in vivo studies have demonstrated lower sodium concentration in subjects with OA (Na-concentration <250 mM) as compared with a healthy population (~300 mM) (32)(33)(34)(35). Due to the low resolution partial volume effects with the the low-sodium concentration synovial fluid (~140 mM) is a confounding factor.…”
Section: Sodium (Na) Imagingmentioning
confidence: 99%